KEEFEKTIFAN MEDIA KOMIK TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS IV SD - Untari, Mei Fita Asri; Saputra, Aprilianta Adi (Universitas Pendidikan Indonesia, 2016)
This research is motivated by the low reading interest of children who have an impact on learning outcome is low and the need to streamline the reading comprehension to be able easily understand the material being studied. This study aims to determine the effectiveness of the medium of comics to the students' reading ability. Based on the analysis of data, the first measurement using the story